A comprehensive hierarchical model of retail banking. Issue 4 (5th June 2017) - Bakar, Juhaida Abu; Clemes, Michael Daniel; Bicknell, Kathryn
Abstract : Purpose: The purpose of this paper is to develop and test a comprehensive hierarchical model of behavioural intentions in the Malaysian retail banking industry. Design/methodology/approach: The data were analysed using EFA, CFA and structural modelling. Findings: The findings illustrate that customer satisfaction is the most important determinant of behavioural intentions, followed by switching costs, corporate image and perceived value. Service quality is indirectly related to behavioural intentions and customer satisfaction mediates the relationship between the two constructs. Customer satisfaction is strongly influenced by service quality, corporate image and perceived value. Service quality is also an antecedent of perceived value, corporate image and switching costs. The empirical results also support a hierarchical and multidimensional approach for conceptualising and measuring customers' perceptions of service quality. Research limitations/implications: The comprehensive hierarchical model developed in this research can be used as framework for additional studies on the banking industry. Practical implications: The findings provide Malaysian bank managers with empirically-based insights into behavioural intentions and offer guidelines for assessing and improving service quality. Originality/value: This is the first study that uses comprehensive hierarchical modelling to synthesise the effects of service quality, customer satisfaction, perceived value, corporate image and switching costs on the behavioural intentions of retail bank customers.